R‐CHOP therapy alone in limited stage diffuse large B‐cell lymphoma - Tomita, Naoto; Takasaki, Hirotaka; Miyashita, Kazuho; Fujisawa, Shin; Ogusa, Eriko; Matsuura, Shiro; Kishimoto, Kumiko; Numata, Ayumi; Fujita, Atsuko; Ohshima, Rika; Kuwabara, Hideyuki; Hagihara, Maki; et al. (British Journal of Haematology, 2013)
Summary Long‐term observation has identified a pattern of continuing relapse in limited stage diffuse large B‐cell lymphoma (DLBCL) treated by three cycles of R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) plus involved‐field irradiation. We retrospectively analysed 190 untreated patients with limited stage DLBCL treated by R‐CHOP alone. All the patients were scheduled to undergo primary therapy with six cycles of full‐dose R‐CHOP. Cases with a dose reduction of more than 20% were excluded from the study. Additional local irradiation was allowed in patients with partial response (PR). Five patients received additional local irradiation after PR at the end of the R‐CHOP therapy. The median observation period was 52 months. Median age at diagnosis was 63 years. The responses to therapy were 180 complete responses, eight PR, and two progression of disease (PD). The 5‐year progression‐free survival and 5‐year overall survival rates were 84% and 90%, respectively, both in plateau. During the observation period, 29 patients experienced PD. The progression sites were the primary sites in 15 patients, outside the primary sites in 10, and undetermined in four patients. These results suggest that the ‘standard’ strategy of three cycles of R‐CHOP followed by involved‐field radiotherapy for limited stage DLBCL could be effectively replaced by six cycles of R‐CHOP alone.